Discrimination in the general population - Silvia Angerer; Hanna Brosch; Daniela Glätzle-Rützler; Philipp Lergetporer; Thomas Rittmannsberger (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2024)
We present representative evidence of discrimination against migrants through an incentivized choice experiment with over 2,000 participants. Decision makers allocate a fixed endowment between two receivers. To measure discrimination, we randomly vary receivers' migration background and other attributes, including education, gender, and age. We find that discrimination against migrants by the general population is both widespread and substantial. Our causal moderation analysis shows that migrants with higher education and female migrants experience significantly less discrimination. Discrimination is more pronounced among decision makers who are male, non-migrants, have right-wing political preferences, and live in regions with lower migrant shares.
Keywords: C91; C93; J15; D90; 330; discrimination; representative sample; migration; experiment